Study on Simulation Test of Peat Soil Environment in Dianchi Lake - Jing Cao; Siyang Huang; Wenlian Liu; Cheng Kong; Yue Gao; Fangyi Liu (Advances in Civil Engineering)
The effect and feasibility of peat soil environment (PSE) simulation pose a difficult problem for geotechnical environmental engineering. In this study, the actual content of humic group (HG) in peat soil of Dianchi Lake is determined, and the method of adding humic acid (HA) reagent into cohesive soil and soaking it in fulvic acid (FA) solution is used to simulate PSE of Dianchi Lake. By comparing the HG content of test samples and natural peat soil, the effect and feasibility of simulation test are studied. And the effects of HG on microstructure and material composition of PSE are analyzed by scanning electron microscopy (SEM) and X-ray diffraction (XRD) tests. The test results show that the content of HG and its components of PSE in seven sites of Dianchi Lake are quite different. The simulation method used in this study can simulate the PSE with different HA and FA contents, but the simulation method of soaking samples in FA solution cannot reach the actual effect. The SEM test confirm that the pore size and pore connectivity will increase with the HA reagent. However, FA is wrapped on the skeleton of soil through adsorption and fills some pores, which reduces the pore diameter and weakens pore connectivity. The XRD test shows that both HA and FA can reduce the diffraction peak of main substances in the samples, but not including SiO2. The reason is that HG and cohesive soil particles undergo coordination exchange and ion exchange; free HG combines with cohesive soil particles and transforms into bound HG, forming an organic-inorganic complex PSE.